Kajian literatur: Peran public relation terhadap strategi marketing pembiayaan pada perbankan Syariah - Fatihah, Ramadina Salwanda (Maliki Interdisciplinary Journal, 2024)
This research aims to find out what roles are played by public relations in financing marketing strategies in sharia banking through 6 articles that are relevant to the research discussed. .This research uses a method in the form of a literature review, namely by collecting data within the scope of scientific publication articles which contain a description or summary of literature related to relevant topicsthus providing an overview of what was discussed.studies show that Islamic banking carries out its activities based on sharia principles and uses financing as the main source of profit .In financing marketing strategies, public relations (PR) is very important, especially in building a positive image, maintaining relationships with customers, and increasing promotions through various media. .Previous studies show that PR functions as a link between banks and the public, supports marketing, and increases public trust and customer loyalty. .Islamic banks are advised to increase community participation, utilize social media, and maintain a positive reputation through cooperation and training on sharia products.